QUALITY OF RENNET FROM RABBIT STOMACH DURING COLD AND FROZEN STORAGE - Nurliyani, Nurliyani; Indratiningsih, Indratiningsih; Mufti Tri, Marta (2013)
Problems in cheese production in Indonesia is the use of milk coagulating enzymes (rennet) for the curd formation, which is still imported. Stomach rabbit is waste of rabbit slaughtering can be used as an alternative in the cheese production. The purpose of this study was to determine the quality of rabbits stomach rennet during cold and frozen storage temperatures. The rennet quality are include the milk coagulating ability, curd yield percentage, pH and proteolytic activity of rennet. Rennet quality data were analyzed statistically using a two-way ANOVA, with three times replication. The results showed that the average of milk coagulation time, curd yield and pH were not significantly different between the rennet stored at cold and frozen temperatures. However, during storage 0; 15 and 30 days occurred significant difference (P< 0.05) on milk coagulation time, curd yield and rennet pH, a started 0; 15 and 30 days: the average coagulation time was 3.35; 3.91 and 4.63 minutes , the average yield of curd (rendemen) was 11.07; 8.93 and 7.47%, and the average of rennet pH was 5.60 ; 5.88 and 5.94, respectively. The proteolytic activity of rabbit stomach rennet stored at frozen temperatures was higher (P <0.05) than the rennet stored at cold temperatures. There was a significant change in proteolytic activity of rennet during storage. At storage 0; 15 and 30 days, the average of proteolytic activity of rennet was 25.87; 24.79, and 24.43 mg / ml / min, respectively. In conclusion, the rabbit stomach rennet stored at cold and frozen temperatures has the same quality in its ability to milk coagulate, curd yield and pH value. However, there were slight changes in the quality of rabbit stomach rennet during 30 days of storage at cold and frozen temperatures, which is an increase in the milk coagulating time, decreasing in curd yield, increasing the pH value and decreasing of proteolytic activity of rennet. Key words: Rennet Quality, Rabbit Stomach, Storage.